Three-dimensional finite element modeling of RC columns subjected to cyclic lateral loading. (15th July 2021) - Fawaz, Ghassan; Murcia-Delso, Juan
Highlights: 3D FE models are proposed integrating cyclic laws for concrete, steel and bond-slip. A classical steel model is modified to account for low-cycle fatigue rupture. A bond-slip model is enhanced to improve its accuracy and computational efficiency. The FE models accurately predict the nonlinear response and failure of column tests. Bar rupture is well captured in both single bar test and large-scale column tests. Abstract: This paper presents a detailed finite element modeling scheme to simulate the cyclic response of RC columns considering low-cycle fatigue and bond-slip of reinforcement. The modeling scheme includes a triaxial constitutive model recently proposed in the literature to simulate concrete failure under cyclic loading. For steel, a commonly used uniaxial model is enhanced to account for bar rupture using a new low-cycle fatigue criterion, which has been validated with data from fatigue tests on reinforcing bars. The bond-slip behavior of vertical reinforcing bars is modeled using a zero-thickness concrete-steel interface element. The interface element has a bond stress-slip constitutive law that predicts bond deterioration caused by generalized slip demands, tensile yielding of steel, and compression damage in concrete. The finite element models are validated with experimental data from cyclic tests on large-scale column and pile specimens which exhibited flexure-dominated responses. The models accurately simulate the lateral force–displacement response and failure of the specimens, and provide peak tensile strain demands along longitudinal bars which are similar to those measured experimentally. Sensitivity analyses are also conducted to study the effect of modeling assumptions related to low-cycle fatigue and bond-slip behavior.